Mitragyna speciosa, a psychoactive tree from Southeast Asia with opioid activity - Adkins, Jessica E; Boyer, Edward W; McCurdy, Christopher R (Current topics in medicinal chemistry, 2011)
Mitragyna speciosa Korth. (Rubiaceae) is a tree that is commonly found in Southeast Asia. Leaves from this tree have been traditionally been used for both their stimulant properties as well as an opium substitute. The tree/leaves are currently illegal in four countries, but is currently legal and widely available in the United States. To date over 40 compounds have been isolated from the leaves. The major alkaloid found within the crude extract, mitragynine, has been the subject of many pharmacological studies. In addition to the pharmacological studies, two total syntheses of mitragynine have been published as well as general structure-activity relationships (SARs) with respect to opioid activity.